2024
DOI: 10.3390/microorganisms12050919
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Microbiota in Coconut Water, Kefir, Coconut Water Kefir and Coconut Water Kefir-Fermented Sourdough Using Culture-Dependent Techniques and Illumina–MiSeq Sequencing

Mansi Limbad,
Noemi Gutierrez Maddox,
Nazimah Hamid
et al.

Abstract: The principal objective of this study was to isolate and identify the microorganisms present in commercial kefir grains, a novel kefir-fermented coconut water (CWK) and a novel coconut water kefir-fermented sourdough using phenotypic identification and Sanger sequencing and examine the microbial diversity of CWK and CWK-fermented sourdough throughout the fermentation process using the MiSeq Illumina sequencing method. The phenotypic characterisation based on morphology identified ten isolates of LAB, five AAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Sourdough (600 g) was prepared using CWK (300 mL), table salt (3 g), and canola oil (1.5 mL). In total, 1 g of sourdough sample was taken every 24 h of fermentation, which was suspended in 9 mL of deionized water using a stomacher (or a mechanical mixer) [27]. All of the identified species of LAB, acetic acid bacteria, and yeasts (Section 3.1) included in this study (Table 1) were isolated and identified from kefir, CWK, and CWK-fermented sourdough as per the study by Limbad et al (2024) [27].…”
Section: Cultures and Culture Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Sourdough (600 g) was prepared using CWK (300 mL), table salt (3 g), and canola oil (1.5 mL). In total, 1 g of sourdough sample was taken every 24 h of fermentation, which was suspended in 9 mL of deionized water using a stomacher (or a mechanical mixer) [27]. All of the identified species of LAB, acetic acid bacteria, and yeasts (Section 3.1) included in this study (Table 1) were isolated and identified from kefir, CWK, and CWK-fermented sourdough as per the study by Limbad et al (2024) [27].…”
Section: Cultures and Culture Mediamentioning
confidence: 99%
“…In total, 1 g of sourdough sample was taken every 24 h of fermentation, which was suspended in 9 mL of deionized water using a stomacher (or a mechanical mixer) [27]. All of the identified species of LAB, acetic acid bacteria, and yeasts (Section 3.1) included in this study (Table 1) were isolated and identified from kefir, CWK, and CWK-fermented sourdough as per the study by Limbad et al (2024) [27]. The phytic-acid-containing medium was prepared from phosphate-free minimal medium, supplemented with 2 g/L of phytic acid dipotassium salt of the highest available purity (Sigma-Aldrich Inc., Auckland, New Zealand).…”
Section: Cultures and Culture Mediamentioning
confidence: 99%